Outcomes of mechanical thrombectomy for medium vessel occlusion in acute ischemic stroke patients with ASPECTS 4-5 vs. 6-7: a retrospective, multicenter, and multinational study - Musmar, Basel; Salim, Hamza Adel; Adeeb, Nimer; Yedavalli, Vivek; Lakhani, Dhairya; El Naamani, Kareem; Henninger, Nils; Sundararajan, Sri Hari; Kühn, Anna Luisa; Khalife, Jane; Ghozy, Sherief; Scarcia, Luca; et al. (Neuroradiology, 2025)
Mechanical thrombectomy (MT) efficacy in medium vessel occlusion (MeVO) stroke, particularly in patients with low Alberta Stroke Program Early Computed Tomography Score (ASPECTS), remains less explored.
Gesehen am 21.11.2025